2003
DOI: 10.1007/s00595-003-2598-z
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Necrosis After an Infarction of the Spleen: Report of a Case

Abstract: Gastric necrosis is a rare and often fatal condition. A few reports of gastric necrosis of various etiologies have been published in the literature. This report deals with a case in which gastric necrosis and perforation occurred several years after an infarction of the spleen. Preoperative computed tomography showed the existence of splenic vein thrombosis accompanying splenic infarction. A laparotomy revealed an 8-cm-long laceration with ragged margins in the posterior of the stomach along the greater curvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…On the other hand, gastric necrosis may be a life-threatening condition due to increased perforation risk [4]. Its etiology includes cardiovascular disease, hypercoagulable state, arterial thrombosis and embolism, hemodynamic compromise, hypoxemia, alcohol ingestion, corrosive substance intake, gastric outlet obstruction, gastric herniation, massive gastric dilatation, volvulus, previous gastric surgery, bulimia, trauma and infection [4][5][6][7]. Based on the information gleaned from the patient's evaluation, the most likely diagnosis is stomach necrosis and perforation due to celiac artery thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, gastric necrosis may be a life-threatening condition due to increased perforation risk [4]. Its etiology includes cardiovascular disease, hypercoagulable state, arterial thrombosis and embolism, hemodynamic compromise, hypoxemia, alcohol ingestion, corrosive substance intake, gastric outlet obstruction, gastric herniation, massive gastric dilatation, volvulus, previous gastric surgery, bulimia, trauma and infection [4][5][6][7]. Based on the information gleaned from the patient's evaluation, the most likely diagnosis is stomach necrosis and perforation due to celiac artery thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, these complications occurred in only 23% of cases in which the left gastric artery had been ligated. Portal hypertension(14) and splenic venous thrombosis(15) (one cause of gastric necrosis) have also been found to impede gastric venous drainage. However, one report found that a single short gastric artery can supply the entire stomach adequately via its intramural vessel connections.…”
Section: Discussionmentioning
confidence: 99%